All you need is air—Alternating activated sludge system BIOCOS without electromechanical equipment. (5th February 2021) - Wett, Bernhard; Brückl, Annemarie; Aichinger, Peter; Ingerle, Kurt
Abstract: Exclusively air‐driven operation is an essential feature of the cyclic activated sludge process BIOCOS. Switching the air‐flow between diffusers, agitation, and recycle air‐lift keeps operation and maintenance simple and leads to significant energy savings used for mechanical devices. The overall energy demand for the whole biological system with settling was found to be below 20 kWh/PE.a. This hybrid technology shows a constant water level characteristic for continuous flow systems and time‐based control. Modular rectangular tank configuration and high solids operation targets a compact footprint. Process wise, the settling sludge blanket in the two alternating settling tanks was found to contribute considerably to post‐denitrification and enhances phosphorus removal. During the last years, approximately 200 BIOCOS plants have been implemented mainly in Germany, Austria, Spain, and China, some of the operational results are presented in this paper. Practitioners points: BIOCOS is a hybrid process with alternating settling tanks at constant water level. The performance of demonstration plants shows high resilience against hydraulic and organic peak loads. The energy demand for the process was found to be very small. The process is driven with no electromechanical equipment but one main blower station. The sludge blanket in the alternating settler significantly contributes to denitrification and phosphorus removal. Abstract : .